Influence of gas mixtures on complex plasmas parameters in rf and dc discharges - Dosbolayev, M. K.; Utegenov, A. U.; Ramazanov, T. S. (Recent Contributions to Physics, 2014)
In this paper the influence of the gas mixture on plasma parameters in DC and combined RF+DC discharge is studied. Тhe properties of complex plasma in the radio-frequency discharge of the gas mixture,with additional constant electrostatic field were experimentally studied. It is shown that the addition of a heavy gas to a light one, and the additional impact of a constant field on the RF discharge leads to changes in the spatial characteristics of the buffer plasma and, hence, the location of the dust structure.
Keywords: radio-frequency capacitive discharge; mixture of gases; combined RF DC discharge